"MODERN APPROACHES TO COGNITIVE LINGUISTICS " (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article discusses the issues of concept typology and classification in modern linguistic conceptology. The article provides information about one-level, multi-level, and segment concepts. In addition, the verbalization of concepts through linguistic units is analyzed using the example of the concept of “literacy.”
Keywords: concept, conceptology, cognitive linguistics, concept typology, concept classification, verbalization, linguo-cognitive analysis, cognitive layer, segment concept, literacy concept.